The good nurse : a true story of medicine, madness, and murder - Graeber, Charles (New York : Twelve, 2013)
After his December 2003 arrest, registered nurse Charlie Cullen was quickly dubbed "The Angel of Death" by the media. But Cullen was no mercy killer, nor was he a simple monster. He was a favorite son, husband, beloved father, best friend, and celebrated caregiver. Implicated in the deaths of as many as 300 patients, he was also perhaps the most prolific serial killer in American history. Cullen's murderous career in the world's most trusted profession spanned sixteen years and nine hospitals across New Jersey and Pennsylvania--Publisher's description.
Includes bibliographical references (pages 277-300) and index.
Keywords: Cullen, Charles,1960-; Serial murderers -- United States -- Biography; Nurses -- United States -- Biography